Credit enhancement factors for the financing of independent power producer (IPP) projects in Asia. Issue 7 (October 2015) - Chowdhury, Abu Naser; Chen, Po-Han; Tiong, Robert L.K.
Abstract Public and private parties give a number of guarantees and commitments in the form of credit enhancement for successful investment and implementation of independent power producer (IPP) projects in Asia. A research is thus conducted to find the suitable credit enhancement factors for these projects. From 27 out of 28 credit enhancement factors that were validated by IPP professionals, factor analysis revealed five factor groupings which are — (1) shareholders' credit enhancement, (2) host government's credit enhancement, (3) multi-lateral development banks (MDBs), export credit agencies (ECAs) and other parties' credit enhancement, (4) capital structure mechanism, and (5) commercial bank's credit enhancement. From these critical credit enhancement groupings, it is further noticed that contingency equity support, standby credit guarantee, subordinated debt mechanism, financing with political risk insurance from MDBs and ECAs, escrow account, and standby letter of credit are of great importance for financing decision of IPP projects in Asia.